21st Century Skills of Professional Nurses of Difference Generations at Tertiary Hospitals under The Royal Thai Army Medical Department - laosena, Sirada; Pongrangsarn, Phattharamanat (Journal of The Royal Thai Army Nurses, 2024)
This cross-sectional survey research aims to study the level of 21st century skills and compare the 21st century skills of professional nurses by age group. The sample group were 261 professional nurses of different age groups working in tertiary hospitals under the Royal Thai Army Medical Department. The instrument was the 21st Century Skills Questionnaire. The overall Cronbach’s alpha coefficient was 0.97. The statistics were frequency, percentage, mean, standard deviation and One-Way ANOVA and Scheffe’s method. The results found that Professional nurses of different ages have overall 21st century skills at a good level ( = 4.08, S.D. = 0.41). Classified by age group, the highest average was Generation X ( = 4.18, S.D. = 0.33), Generation Z ( = 4.16, S.D. = 0.36) and Generation Y ( = 4.02, S.D. = 0.43), respectively. The highest mean was that Cross–cultural Understanding skills at a very good level ( = 4.46, S.D. = 0.52). The lowest average is that Writing skills at a good level ( = 3.71, S.D. = 0.55). Professional nurses of different age groups have significantly different skills in the 21st century at .05 (F = 4.034). The results of this research provide basic information for nursing administrators to apply the research results as a guideline for planning the development of skills, knowledge and work assignments in line with the aptitude and skills of professional nurses. To provide professional nurses with the skills and knowledge to perform well in the 21st century.